Peran musyrif/ah dalam penanganan masalah kesehatan mental mahasantri : studi kasus di ma’had uin malang - Septiano, Nabil Muzakki (Maliki Interdisciplinary Journal, 2025)
In the world of higher education, especially in campus pesantren or Ma’had, the phenomenon of increasing mental health problems among students is a serious concern. Students face many challenges of academics, religious obligations, and social life in a closed environment. As the main companion of the mahasantri in daily life, musirif/ah may play an important role in psychological assistance. Using a qualitative case study method, this research aims to explain the role of musyrif in addressing mahasantri mental health issues. The results showed that musyrifs are not just supervisors; they also function as unofficial counselors, conflict mediators, and emotional support providers. These results increase understanding of the role of non-professionals in community-based psychological support systems and encourage musyrif/ah to get basic counseling training.